An Analysis of Personality Styles; Does mathematics anxiety change with adversity Quotient? - Widodo Winarso (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2023)
This research aims to categorize the mathematics anxiety and adversity quotient in students and describe the profile of mathematics anxiety in students based on the adversity quotient. This research method is qualitative with a case study design. The subjects of this study were 45 students of SMPIT Sabilul Huda. The data collection instruments used were the Taylor Manifest Anxiety Scale (TMAS), the Adversity Quotient Response Profile (ARP) scale, and interview guidelines. Data analysis techniques used are data reduction, data presentation, and conclusion. From this study, it was found that (1) the level of mathematics anxiety at SMPIT Sabilul Huda was in the category of severe anxiety, (2) the level of AQ at SMPIT Sabilul Huda was in the category of campers, (3) the profile of mathematics anxiety based on AQ was divided into 9 categories, namely the category of severe anxiety and climbers (B-Cl), severe anxiety and campers (B-Cm), severe anxiety and quitters (BQ), moderate anxiety and climbers (S-Cl), moderate anxiety and campers (S-Cm), moderate anxiety and quitters ( SQ), mild anxiety and climbers (R-Cl), mild anxiety and campers (R-Cm), mild anxiety and quitters (RQ)